Norms of the Council of Europe in the Postsoviet Space: National Minorities in the Republic of Armenia and the Framework Convention for the Protection of National Minorities - Chilingaryan, Gagik (Pécs journal of international and European law, 2023)
The present paper includes activities of Framework Convention for the Protection of National Minorities (FCNM), which is Europe’s most comprehensive treaty protecting the rights of persons belonging to national minorities in the territory of South Caucasus focusing on The Republic of Armenia. The paper the instruments and mechanisms of protection of national minorities in the republic. It aims to analyze FCNM monitoring cycles, focusing on recommendations by Council of Europe and Reports by the government of the Republic of Armenia as well as Opinions by Advisory Committee of FCNM, considering the influence of Constitutional amendments of 2015 and the “Velvet Revolution” of 2018 in the Republic of Armenia if they are. The paper helps to understand the causes of problems in fulfillment of obligations undertook by the Republic of Armenia in the sphere of national minority protection.